Terminal Dilemma: Hong Kong’s Waterfront, 1841-1891 - Davies, Stephen (Australasian Journal of Victorian Studies, 2015)
At each end of a transport route comes the terminus. The place where the journey symbolically begins or ends. Victorian transport often seems symbolized by grand termini – think Euston, St Pancras, Gare Austerlitz, Victoria Terminus Mumbai. Sea transport in the Victorian era was different. Especially in colonial outposts. For the major part of Queen Victoria’s long reign arriving and departing by sea in Hong Kong was a workaday and rugged encounter with the levelling verities of water transport. A ferry or small coaster alongside a rough and ready jetty. A bumboat ride to or from a ship, usually sail not steam, moored or anchored in the stream. And at the interface between sea and land a stinking, befouled shoreline issuing onto a working waterfront hugger-mugger with loading and unloading onto a muddy road backed by offices, warehouses, shipyards and slipways. Waterfront development in Hong Kong was from the outset piecemeal, uncoordinated and unplanned. Only in the last decade and a half of the nineteenth century did the colonial government show the first glimmers of interest in port planning and development. For most of the fifty years from 1841-1891, the waterfront was a random muddle of dockyards, slipways, jetties, nullahs, promenades, sewage outlets, and the fronts and backs of buildings. It was also divided between a maritime East and a maritime West.